New receptor with a FRET based fluorescence response for selective recognition of fumaric and maleic acids in aqueous medium - Reddy, Upendar G.; Lo, Rabindranath; Roy, Sovan; Banerjee, Tanmay; Ganguly, Bishwajit; Das, Amitava (Chemical Communications, 2013)
Preferential binding of a new reagent to fumaric acid could be utilized for its estimation in aqueous medium and in commercial fruit juice.